Dynamic Analysis and Experimental Verification of a Multi-Degree-of-Freedom Eddy Current Damper in a Cryogenic Environment - Yudai Umekawa; Akira Heya; Shinsaku Nakamura; Tsuyoshi Inoue (IEEE Access)
Reusable rockets are under development and have received considerable attention. The large rockets and reusable vehicles under development in Japan use liquid hydrogen, and their turbopumps require high-speed rotation. However, this approach causes vibrational problems. A wire-mesh damper has been used to reduce shaft vibration; however, it uses a friction force, causing wear and being unsuitable for dampers of reusable rockets in terms of life-cycle cost. Eddy current dampers play a significant role in solving these problems. The eddy current dampers reduce vibration without any mechanical contact; however, conventional eddy current damper structures are unsuitable for reducing multiple-degree-of-freedom (multi-DOF) vibrations. Therefore, a novel structure for a multi-DOF eddy current damper for liquid-hydrogen turbopumps is proposed in this paper. The damping performance of the proposed eddy current damper is superior to that of the existing multi-DOF eddy current damper by analyzing the damping performance of the structural model at an ambient temperature using a two-dimensional finite element method. Further, the damping performance of the proposed damper at various temperatures, from ambient temperature to cryogenic temperatures, is compared. Moreover, the effect of aluminum electrical conductivity attributed to the decrease in temperature is shown to affect not only damping but also the magnetic stiffness and skin effect and the vibration pattern. Finally, experiments were conducted on actual equipment to confirm the effects of the material properties and temperature on eddy current dampers.